2021
DOI: 10.5194/tc-15-2939-2021
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice thickness from air-coupled flexural waves

Abstract: Abstract. Air-coupled flexural waves (ACFWs) appear as wave trains of constant frequency that arrive in advance of the direct air wave from an impulsive source travelling over a floating ice sheet. The frequency of these waves varies with the flexural stiffness of the ice sheet, which is controlled by a combination of thickness and elastic properties. We develop a theoretical framework to understand these waves, utilizing modern numerical and Fourier methods to give a simpler and more accessible description th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Poisson's ratio varies between 0.25 and 0.4 and Young's modulus between 2 and 6 GPa (Anderson, 1958;Timco and Weeks, 2010). In particular, in Van Mijen Fjord, Romeyn et al (2021) reported a Young modulus around 2.5 GPa with a Poisson ratio of 0.33, and Morozov et al (2011) reported a Young modulus around 3 GPa and a Poisson ratio of 0.3. Moreau et al (2014a) reported a Young modulus around 4 GPa and a Poisson ratio of 0.32 at Vallunden.…”
Section: Estimation Of the Probability Density Function Of The Ice Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Poisson's ratio varies between 0.25 and 0.4 and Young's modulus between 2 and 6 GPa (Anderson, 1958;Timco and Weeks, 2010). In particular, in Van Mijen Fjord, Romeyn et al (2021) reported a Young modulus around 2.5 GPa with a Poisson ratio of 0.33, and Morozov et al (2011) reported a Young modulus around 3 GPa and a Poisson ratio of 0.3. Moreau et al (2014a) reported a Young modulus around 4 GPa and a Poisson ratio of 0.32 at Vallunden.…”
Section: Estimation Of the Probability Density Function Of The Ice Pa...mentioning
confidence: 99%
“…Seismic methods based on noise interferometry (Shapiro and Campillo, 2004;Sabra et al, 2005) have solved this problem, and seismic acquisitions applied to sea ice are now possible without the need of human intervention, other than for the installation and removal of the geophones (Marsan et al, 2012(Marsan et al, , 2019Moreau et al, 2020a, b). Another seismic method that was presented by Romeyn et al (2021) makes it possible to estimate the thickness of sea ice. This consists of exploiting the propagation of air-coupled flexural waves that are excited by an impulsive seismic source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the miniaturization of electronic components, the rapid progress in terms of battery life and the era of seismic-noise interferometry (Shapiro and Campillo, 2004;Sabra et al, 2005), it has become possible to collect data without the need of active, human-controlled sources and then to process them remotely (Marsan et al, 2019). Therefore, over the past decade, there has been a renewed interest in seismic methods as a complementary means of monitoring the thickness, density and elastic properties of sea ice (Marsan et al, 2012;Moreau et al, 2020a, b;Romeyn et al, 2021;Serripierri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With the miniaturisation of electronic components, the rapid progress in terms of battery life, and the era of seismic noise interferometry (Shapiro and Campillo, 2004;Sabra et al, 2005), it has become possible to collect data without the need of active, human-controlled sources, and then to process them remotely (Marsan et al, 2019). Therefore, over the past decade, there has been a renewed interest in seismic methods as a complementary means of monitoring sea ice (Marsan et al, 2012;Moreau et al, 2020a, b;Romeyn et al, 2021;Serripierri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%